2018
DOI: 10.1080/02688697.2018.1494265
|View full text |Cite
|
Sign up to set email alerts
|

Use of cyanoacrylate to prevent cerebrospinal fluid fistulas after cranial surgery

Abstract: CA can help dural repair against the development of CSF fistula by taking effect quickly. Also, it is a rapid anti-haemorrhagic agent. It can also be used after posterior fossa surgery, skull base surgery where dural repair is difficult, or during sinus repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Many previous studies have used fibrin sealant for CSF leakage and showed the effectiveness of dura mater sealing; however, a disadvantage of fibrin sealant is its lack of sealing strength 1,2,5 . Other adhesives such as cyanoacrylate and biopolymers with aldehyde-based crosslinkers are used because of their high bonding strength 6–9 . However, the use of these materials is limited owing to their cytotoxicity and low biocompatibility 4,9 …”
mentioning
confidence: 99%
“…Many previous studies have used fibrin sealant for CSF leakage and showed the effectiveness of dura mater sealing; however, a disadvantage of fibrin sealant is its lack of sealing strength 1,2,5 . Other adhesives such as cyanoacrylate and biopolymers with aldehyde-based crosslinkers are used because of their high bonding strength 6–9 . However, the use of these materials is limited owing to their cytotoxicity and low biocompatibility 4,9 …”
mentioning
confidence: 99%